Накопичення кобальту в організмі прісноводних риб за його підвищеного вмісту у воді - Марків, В.С.; Хоменчук, В.О.; Курант, В.З. (Доповіді НАН України, 2023)
Досліджено особливості кількісного накопичення кобальту в організмі карася та щуки за різної його концентрації в оточуючому водному середовищі. Встановлено залежність між вмістом металу у воді і його накопиченням у зябрах, печінці та скелетних м’язах. Підвищені концентрації кобальту у водному середовищі (0,1 та 0,25 мг/дм³) призводять в основному до акумулювання металу в тканинах досліджених видів риб. Більш значне зростання цього показника спостерігається за вищої концентрації металу у воді. The peculiarities of the quantitative accumulation of cobalt in the body of crucian carp and pike at different concentrations in the surrounding water environment were studied. The relationship between the metal content in water and its accumulation in the gills, liver, and skeletal muscles was established. Elevated concentrations of cobalt in the aquatic environment (0.1 and 0.25 mg/dm³) primarily lead to the accumulation of the metal in the tissues of the studied fish species. A more pronounced increase in this indicator is observed with a concentration of 0.25 mg dm³ of the metal in the water. The degree of cobalt accumulation in fish tissues follows a specific order: liver, muscles, gills.